1996
DOI: 10.1084/jem.184.5.1781
|View full text |Cite
|
Sign up to set email alerts
|

Decreased tumor surveillance in perforin-deficient mice.

Abstract: SummaryImmune surveillance against tumors usually depends on T cell recognition of tumor antigens presented by major histocompatibility complex (MHC) molecules, whereas MHC class I tumors may be controlled by natural killer (NK) cells. Perforin-dependent cytotoxicity is a major effector function ofCD8 + MHC class I-restricted T cells and of NK cells. Here, we used perforin-deficient C57BL/6 (PKO) mice to study involvement of perforin and Fas ligand in tumor surveillance in vivo.We induced tumors in PKO and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
216
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(235 citation statements)
references
References 44 publications
19
216
0
Order By: Relevance
“…Although the identity of the FasL-independent mechanisms of tumor regression remains to be fully defined in this model, one possibility includes perforin, based in part on our CMA blocking studies (Figs. 1 and 3) and extrapolation of work by others (6,7,18).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the identity of the FasL-independent mechanisms of tumor regression remains to be fully defined in this model, one possibility includes perforin, based in part on our CMA blocking studies (Figs. 1 and 3) and extrapolation of work by others (6,7,18).…”
Section: Discussionmentioning
confidence: 87%
“…The contribution of each effector mechanism to the overall lytic response probably reflects or depends upon intrinsic characteristics of the given target cell population. Although the prevailing view, particularly in mouse studies, is that perforin/granzyme-mediated lysis is a dominant pathway (6,7,18), it is unclear whether FasLmediated cytotoxicity is additionally required for optimal tumor regression. Accordingly, we investigated here the role of the FasL pathway in Ag-specific CTL-mediated tumor regression by adoptive immunotherapy using this CTL/CMS4 model.…”
mentioning
confidence: 99%
“…3 About 50 years later, the seminal work brought up by Burnet and Thomas supported the concept of tumor immunosurveillance. 4,5 Later, gene targeting, 6 transgenic mouse technologies 7 and highly specific neutralizing monoclonal antibodies targeting particular immune components 8 have allowed to formally identify the key components of anticancer immune responses.…”
Section: Antitumoral Immune Response and Immunosubversionmentioning
confidence: 99%
“…Similarly, studies in tumor-bearing, perforin-deficient mice have also shown a major contribution of perforin to regression of established tumors (12,13). However, many of the tumors used in these previous studies were intrinsically resistant to Fas-mediated killing (9), and some of these experimental models used xenotransplantation of human tumors into mice (12,13). In such experimental systems, the species-specific activities of some cytokines and the strength of xenogeneic immune responses may mask relevant biological roles for cytokines and FasL-mediated effects.…”
mentioning
confidence: 91%